Safety risk assessment of deep excavation for metro stations using the second improved CRITIC cloud model - Wen, Zhou; Amizatulhani, Abdullah; Xu, Xinyu (MDPI, 2025)
The safety risk evaluation of foundation pit excavations in metro stations involves multiple factors with randomness and fuzziness. This study improves the Second Improved CRITIC-Cloud Model for more precise risk assessment. The approach integrates coefficients of variation-based weighting, absolute correlation adjustments, and multidimensional cloud modeling with set pair theory. A dynamic depth-based normalization technique reduces indicator biases. Using Hefei Metro Line 7 Phase I as a case study, we analyzed seven indicators across nine construction stages. The results show that the building settlement (A2) and horizontal displacement of the support structure (A7) have the greatest impact. Comparative analysis with entropy-based methods confirms the model’s effectiveness in capturing risk transitions and improving decision making.